A Different Approach to Fund-Flow Problems. - Snudden, Leslie W. (The Accounting Review, 1965)
Abstract The article focuses on the fund-flow problems which cause the student to think about the interrelationships existing between balance-sheet accounts and income-statement accounts. As a result of this thinking, the student develops a workable understanding of the whole process of accrual accounting. Problems requiring a statement of working-capital flow or a statement of cash flow are excellent devices for teaching accounting. There is a method applicable to solving fund-flow problems which provides some of the advantages of both the worksheet approach and the T-account approach. This method requires the construction of a form which may be thought of as a quasi worksheet or working paper. Through the use of this form the student can see the intermediate steps necessary to solve the whole problem, and he can sense the advantages of a well-organized solution. A completed working paper includes a well-designed working copy of the fund-flow statement. A formal fund-flow statement can be copied directly from the working paper without extensive interpretation of the data.